The Effectiveness of Online Platform Utilization (Instagram) in Islamic Religious Education: A Case Study at SMAN 2 Sarolangun - Zayyan Al-Fazia Fikri, Ely Surayya (Journal of Educational Studies, 2025)
This study investigates the effectiveness of Instagram as an online platform in Islamic Religious Education (PAI) learning at SMAN 2 Sarolangun. Employing a qualitative approach with a case study design, this research involved 30 students of class XII F3 and PAI teachers as research subjects. Data were collected through observation, semi-structured interviews, and documentation, then analysed using the Miles and Huberman interactive model with source and technique triangulation to ensure validity. The findings reveal three dominant patterns of Instagram utilization: passive content consumption, active content creation, and interactive digital discussion. Several supporting factors were identified, including students' pre-existing familiarity with the platform, the abundance of Islamic educational content, and the flexibility of the Kurikulum Merdeka framework. Instagram positively impacted students' learning motivation by presenting PAI material in visually engaging and contextually relevant formats. Furthermore, guided Instagram engagement cultivated key dimensions of Islamic digital literacy character, including tabayyun (information verification), tasamuh (tolerance), and adab (digital ethics). However, risks of distraction and unequal internet access remain critical challenges requiring structured pedagogical intervention.